Factors Affecting Health Behavior In Female Students During Menstruation At The Ruhul Islam Anak Bangsa (Riab) Islamic Boarding School In Ie Eye, Aceh Besar Regency In 2023 - Darmiati, Darmiati; Irdi Salsabila , Putri (Aceh Sanitation Journal, 2023)
Menstrual Hygiene needs to be done early as an effort to prevent health problems such as Reproductive Tract Infections (ISR). Adolescent girls who behave in poor menstrual hygiene have a 1.4-25.07 times greater risk of developing Reproductive Tract Infections (ISR) and women who have a history of ISR have a greater risk of infertility and cervical cancer. This study aims to determine the factors that influence health behavior in female students during menstruation at the Ruhul Islam Anak Bangsa (RIAB) Mata Ie Islamic Boarding School, Aceh Besar Regency in 2023. The factors studied include knowledge, attitudes, actions, beliefs in myths, and sanitation facilities. This study used a cross-sectional study design with a total of 218 students. The results of this study showed that most respondents did not believe in the myth of menstrual hygiene (95.0%). Based on the results of the study, there is 1 variable related to menstrual hygiene in Pesantren Ruhul Islam Anak Bangsa (RIAB), namely sanitation facilities (P-Value = 0.000). Based on the results of data processing, it is known that santiwati changes pads less than 3-4 times a day, does not wash female organs properly, does not dry the genitals after washing them, and does not wash her hands before and after changing pads. Efforts that can be made in this case are to collaborate with Pukesmas, Health Offices, Public Health Extension in providing counseling so that the knowledge obtained by students is not wrong and can be converted into a positive attitude and good behavior.